Legal basis of labor organization of arrested in penitentiary institutions of Ukraine - Жук, Леонід Аркадійович; Жук, Інесса Леонідівна; Неживець, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article considers the organization and some details of arrested people which are detained in special institutions. Also the article considers the practical recommendations on modernization of using the labor work of arrestedpeople and the necessity of creation legal-normative norms on organization of labor work of arrested people.